Corrosion of Additively Manufactured Metallic Implants (Transactions on Additive Manufacturing Meets Medicine, 2020)
The corrosion resistance of an implant material affects its functionality and durability and is a prime factor governing biocompatibility. The introduction of additively manufactured (AM’ed) dental, orthopedic, maxillofacial, and other implants raises a new challenge to corrosion engineers. AM’ed cellular and other structures often contain inherent crevices. In addition, higher level of porosity, less homogeneous microstructures, and higher residual stresses might all degrade the corrosion resistance, not only the mechanical properties, compared to wrought alloys. Furthermore, surface treatments such as electropolishing and electroplating may also be more challenging when dealing with cellular structures. This presentation highlights the challenges in corrosion control of implants in general, and of AM’ed metallic implants in particular.References: [1] S.-B. Hong, N. Eliaz, E.M. Sachs, S.M. Allen and R.M. Latanision, “Corrosion Behavior of Advanced Ti-Based Alloys Made by Three-Dimensional Printing (3DPÔ) for Biomedical Applications,” Corros. Sci., 43(9) (2001) 1781-1791. [2] N. Eliaz, “Corrosion of Metallic Biomaterials: A Review,” Materials, 12(3) (2019) 407.
Keywords: corrosion resistance